Análise de genes e proteínas envolvidos no estado redox de reticulócitos e eritrócitos de pacientes beta talassêmicos ou com anemia falciforme - Romanello, Karen Simone (2018)
Although not the primary etiology of diseases such as beta-thalassemia and sickle cell anemia, oxidative damage plays a crucial role in the aggravation of these diseases, contributing to the hemolysis and the short survival of the red cells in the circulation. Among the mechanisms to combat oxidative stress are the enzymatic antioxidant defenses such as SOD1, CAT, GPX1, and PRDXs, and the latter stand out for their abundance and high reactivity with their substrates. The main objective of this study was to associate the levels of PRDXs 1, 2 and 6 and its reducers TRX1, TRXR1 and SRX1 with the high ROS production observed in patients with beta-thalassemia intermedia (BTI) and sickle cell anemia. In addition, we analyzed the production of SOD1, CAT, and GPX1, as well as the NRF2/KEAP1/PKCδ complex, known to regulate the expression of enzymes involved in this work. For comparative purposes, we analyzed the protein levels of PRDXs 1, 2 and 6 in patients with the beta-thalassemia major phenotype (BTM). Our results showed significantly increased levels of PRDX1 in BTI when compared to healthy subjects and BTM, whereas PRDX2 was shown to be higher in BTM. However, the superoxidation levels of this enzyme are also higher in these patients, suggesting that the recycling of this enzyme is limiting the overall catalytic cycle. In addition, we observed an increase in the levels of TRX1 and SOD1 in BTI compared to healthy individuals, indicating an additional mechanism to reduce the high levels of ROS observed in these patients. Our data also suggest the participation of the NRF2 transcription factor in the regulation of the antioxidant enzymes analyzed in this work. With regard to patients with sickle cell anemia, the results obtained when compared to those of healthy individuals showed: reduction of the protein content of PRDX2, indicating a greater vulnerability of these cells to the EROS attack. In the extracellular environment, PRDXs 1 and 2 showed an expressive increase in the analyzed patients. The NRF2/KEAP1/PKCδ complex showed a significant reduction in their gene expression, indicating a possible limitation of the antioxidative response in these patients. Our data broaden the knowledge of the literature and reveal the regulation of new targets that can be evaluated for a better understanding of these diseases.